Elastic conductive nanofiber-based multifunctional composite membrane material as well as preparation method and application thereof
The synthetic conductive nanofiber composite film is solved by electrospinning and in-situ reduction technology, and the existing electromagnetic shielding materials have been solved, and the lightweight, flexible and efficient electromagnetic shielding effect is achieved.
Patent Information
- Application Number
- CN202411494411.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-02-25
AI Technical Summary
The existing electromagnetic shielding materials have high density, poor flexibility and complex processing, which are difficult to meet the development needs of lightweight portable electronic devices. The lack of solid bonding between nanofibers, resulting in low mechanical strength and discontinuity of conductive networks.
Through electrospinning and in-situ reduction, the conductive nanofiber composite film is rapidly synthesized, and the uniform mixing of polymer polymers and metal salts is used to form a continuous and stable conductive network to improve electromagnetic wave shielding performance.
The prepared elastic conductive nanofiber matrix composite material has the characteristics of lightweight, breathable and moisture permeable, elastic and flexible, which significantly improves the electromagnetic wave shielding performance and can achieve high electromagnetic shielding effect under low metal content.
Smart Images

Figure CN119507124A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of conductive material preparation, and in particular to an elastic conductive nanofiber-based composite material and a preparation method and application thereof. Background Art
[0002] With the rapid development of modern communication technology, people's demand for the operation of electronic equipment is gradually developing in the direction of lightweight and miniaturization. The electromagnetic interference and electromagnetic radiation generated by electronic equipment not only affect human health, but also affect the normal operation of precision equipment. In order to reduce or suppress the impact of electromagnetic radiation, the demand for thinner, lighter and stronger electromagnetic shielding materials is increasing. In addition, with the rapid development of wearable electronic technology, it is of great significance to develop electromagnetic shielding materials with good comfort.
[0003] Electromagnetic shielding materials use shielding bodies to suppress or weaken the propagation of electric and magnetic fields corresponding to electromagnetic waves, thereby shielding electromagnetic waves. Traditional metal-based electromagnetic shielding materials have high conductivity and excellent shielding effectiveness, but they have disadvantages such as high density, poor flexibility, and complex processing, making it difficult to meet the development needs of lightweight portable electronic devices. Nanofibers have the characteristics of being porous, high aspect ratio, soft, and lightweight, and are easy to compound with metal nanoparticles, which can greatly reduce the density of metal-based composite materials while improving their flexibility and processability.
[0004] In order to achieve uniform distribution of metal in polymer nanofibers, a common method is to modify the surface of polymer nanofibers to enhance the bonding force between metal and fiber matrix, thereby constructing metal-based polymer nanofiber composites. However, fiber surface modification will destroy the polymer molecular structure and reduce its toughness on the one hand, and increase time and cost on the other hand. In addition, nanofibers are stacked layer by layer, and there is no strong bonding force between fibers, resulting in low mechanical strength and not conducive to the construction of long continuous conductive networks. Therefore, it is of great significance to construct and realize the simple and rapid growth of metal nanoparticles on embedded nanofibers to obtain flexible ultra-long conductive nanofiber networks. Summary of the invention
[0005] The present invention solves the problems in the above prior art by providing an elastic conductive nanofiber-based composite material. The conductive nanofiber composite membrane rapidly synthesized by electrospinning and in-situ reduction has the characteristics of light weight, air permeability, moisture permeability, elasticity, flexibility, etc., and effectively improves the electromagnetic wave shielding performance. Specifically:
[0006] A method for preparing an elastic conductive nanofiber-based multifunctional composite membrane material, comprising:
[0007] Step S1, adding a metal salt to an organic mixed solvent and mixing evenly, then adding a high molecular polymer and continuing to mix to obtain an electrospinning solution; selecting a mixed organic solvent can help dissolve the high molecular polymer while reducing the boiling point of the mixed solvent, which is beneficial to the volatilization of the organic solvent during the spinning process;
[0008] Step S2, injecting the electrospinning solution into a syringe to prepare a metal salt / polymer nanofiber composite membrane by electrospinning;
[0009] Step S3, placing the prepared metal salt / nanofiber composite membrane in a reducing solution for reduction, and obtaining a metal / nanofiber composite membrane after drying.
[0010] Optionally, in step S1, the metal salt is selected from at least one of silver nitrate, silver trifluoroacetate, silver acetate, and copper trifluoroacetate.
[0011] Optionally, in step S1, the high molecular polymer is a thermoplastic elastomer, such as polyurethane or polyester rubber with hydroxyl groups; the organic mixed solvent is selected from two or more of acetone, dichloromethane, N,N-dimethylformamide, and tetrahydrofuran, for example, the volume ratio of N,N-dimethylformamide to acetone or dichloromethane or tetrahydrofuran is 7:3-3:1.
[0012] Optionally, in step S1, the concentration of the metal salt in the electrospinning solution is 1-13 wt %. When the metal salt is too little, the electromagnetic shielding performance of the obtained composite film is poor, and when the metal salt is too much, the solution cannot be spun.
[0013] Optionally, in step S2, the process conditions of the electrospinning process are voltage 10~22 kV, propulsion speed 0.1~3mL / h, receiving distance 10~20 cm, temperature 20~60°C, and humidity 5%~40%.
[0014] Optionally, in step S3, the reducing solution is selected from at least one of sodium borohydride, ascorbic acid, and hydrazine hydrate; the mass concentration of the reducing solution is 50 mg / mL~800 mg / mL, the reduction time is 5~60 min, and the reduction temperature is 25~90 °C.
[0015] The elastic conductive nanofiber-based composite material prepared by the method of the present invention can be used as an electromagnetic shielding material. The high molecular polymer and the metal salt are uniformly mixed to prepare a spinning solution, and the electrostatic spinning and in-situ reduction technology are used to form a composite fiber membrane with a continuous and stable conductive network, which is helpful to improve the electromagnetic shielding ability.
[0016] An application of the elastic conductive nanofiber-based composite material described above is to use the elastic conductive nanofiber-based composite material for electromagnetic shielding performance testing.
[0017] Preferably, the composite material has a thickness of less than 0.25 mm, and an electromagnetic shielding performance greater than 70 dB, preferably greater than 95 dB, when the loaded metal content is less than 37%, and can shield almost 100% of the incident electromagnetic waves.
[0018] The elastic conductive nanofiber-based composite material prepared by the method of the present invention can be used as a wearable device for human body. The continuous and interconnected conductive network makes the composite material have excellent conductivity, which is helpful to improve the electric heat conversion ability.
[0019] An application of the elastic conductive nanofiber-based composite material described above is to use the elastic conductive nanofiber-based composite material for Joule thermal performance and air permeability and moisture permeability tests.
[0020] Preferably, the composite material can be quickly heated to 85.6°C under a DC voltage of 0.65 V and can be used as an electric heating material in cold environments. The composite material also has a high air permeability greater than 8.2 mm / s and a thermal conductivity greater than 3880 g / (m 2 ·24h) high moisture permeability, allowing good transmission between the skin surface and air and water vapor, comfortable to wear, and can be used as an electric heating material and electromagnetic shielding material in the field of wearable devices for the human body.
[0021] The technical solution of the present invention has at least the following beneficial effects compared with the prior art:
[0022] The conductive nanofiber composite membrane prepared by the present invention avoids the agglomeration of nanoparticles and provides a continuous and stable electron transmission path. In addition, the abundant and interconnected pores in the conductive nanofiber composite membrane provide a path for the multiple scattering / reflection of the incident electromagnetic wave inside the material, greatly improving the electromagnetic shielding performance. The high molecular polymer in the present invention has abundant hydroxyl groups, which helps to adsorb metal ions into the fiber and subsequently uniformly load the metal nanoparticles on the surface to obtain a continuous conductor. Secondly, the high molecular polymer contains abundant intermolecular hydrogen bonds, which helps to form physical crosslinks, so that the obtained nanofibers have mutually embedded overlapping structures and are elastic and porous, which helps to form an ultra-long continuous conductive network after the metal nanoparticles are loaded, thereby improving the reflection and absorption of electromagnetic waves and improving the electromagnetic shielding performance.
[0023] When preparing the composite fiber membrane, the conductive filler selected is metal Ag with high conductivity. The electromagnetic shielding performance of the composite membrane prepared by Cu is worse than that of Ag, which can effectively shield electromagnetic waves. The polymer achieves physical cross-linking through intermolecular hydrogen bonds to form a fiber-embedded overlapping structure, and the -OH in the elastomer can react with the dissociated negative ions in the organic metal salt, such as CF3COO -The ion-dipole interaction is formed to enhance the adsorption of the elastomer to metal ions, so that the organic metal salt and the elastomer can form a uniform and stable electrospinning solution after mixing. Physical crosslinking provides strong connection points between nanofibers, which is not only conducive to improving the elasticity and mechanical strength of the nanofiber membrane, but also makes the fibers more closely connected, greatly expands the electron transmission path, and effectively reduces the contact resistance of the composite fiber membrane. Therefore, a fiber composite membrane with a continuous and stable conductive network is prepared, which has a higher electromagnetic shielding performance. The fiber composite membrane prepared by the present invention has the characteristics of "flexibility, light weight, and high strength". BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0025] Figure 1 This is a SEM image of the elastic conductive nanofiber-based composite material prepared in Example 1.
[0026] Figure 2 This is the XRD pattern of the elastic conductive nanofiber-based composite material prepared in Example 1.
[0027] Figure 3 This is a graph showing the electromagnetic shielding performance of the elastic conductive nanofiber-based composite material prepared in Example 1.
[0028] FIG4 is a physical display diagram of the elastic conductive nanofiber-based composite material prepared in Example 1 under different tensile strains, wherein FIG4 (a) is a tensile strain of 0%, and FIG4 (b) is a tensile strain of 100%.
[0029] Figure 5 This is the tensile stress-strain curve of the elastic conductive nanofiber-based composite material prepared in Example 1.
[0030] Figure 6 This is a curve showing the temperature change over time of the elastic conductive nanofiber-based composite material prepared in Example 1 at a DC voltage of 0.65 V. DETAILED DESCRIPTION
[0031] The technical solution of the present invention is described below.
[0032] In the embodiments of the present invention, words such as "exemplarily" and "for example" are used to indicate examples, illustrations or explanations. Any embodiment or design described as "example" in the present invention should not be interpreted as being more preferred or more advantageous than other embodiments or designs. Specifically, the use of the word "example" is intended to present the concept in a specific way. In addition, in the embodiments of the present invention, the meaning expressed by "and / or" can be both, or it can be either of the two.
[0033] In the embodiments of the present invention, sometimes a subscript such as W1 may be mistakenly written as a non-subscript such as W1. When the difference is not emphasized, the meanings to be expressed are consistent.
[0034] In order to make the technical problems, technical solutions and advantages to be solved by the present invention more clear, a detailed description will be given below with reference to the accompanying drawings and specific embodiments.
[0035] Example 1
[0036] This embodiment provides a method for preparing an elastic conductive nanofiber-based composite material, comprising the following steps:
[0037] S1. Add 0.25 g of silver trifluoroacetate to a mixed solvent of 3 mL of acetone and 9 mL of N,N-dimethylformamide, then add 1 g of thermoplastic polyurethane (TPU), stir magnetically for 12 h to mix evenly, seal the beaker with a sealing film during the stirring process to prevent the solvent from volatilizing, until the solvent is completely dissolved to obtain an electrospinning solution;
[0038] S2, the electrospinning solution was transferred into the syringe, and the electrospinning parameters were set as follows: the distance between the syringe needle and the roller collection device was 10 cm, the voltage was 10 / -2 kV, the spinning solution feed rate was 0.1 ml / h, the spinning time was 2h, and the silver trifluoroacetate / TPU composite fiber membrane was prepared by electrospinning technology;
[0039] S3. The prepared silver trifluoroacetate / TPU composite fiber membrane was placed in a hydrazine hydrate solution with a concentration of 50 mg / mL for reduction reaction for 5 min. After the reaction, it was rinsed with deionized water and placed in a forced air drying oven at 60 °C for 2 h to obtain a conductive Ag / TPU nanofiber membrane.
[0040] An application of the elastic conductive nanofiber-based composite material prepared in this embodiment is to test the elastic conductive nanofiber-based composite material as an electromagnetic shielding material. The material has an electromagnetic shielding performance of 95 dB in the band of 8.2-18 GHz when the thickness is less than 0.25 mm, and can shield almost 100% of the incident electromagnetic waves.
[0041] An application of the elastic conductive nanofiber-based composite material prepared in this embodiment is to use the elastic conductive nanofiber-based composite material as an electric heating material to test Joule heat performance and air permeability and moisture permeability. The material can quickly heat up to 85.6°C under a DC voltage of 0.65 V, and has a high air permeability of 8.2 mm / s and a moisture permeability of 3880 g / (m 2 ·24h) high moisture permeability, and can be used as a wearable electric heating material for the human body.
[0042] Example 2
[0043] This embodiment provides a method for preparing an elastic conductive nanofiber-based composite material, comprising the following steps:
[0044] S1. Add 1.25 g of copper trifluoroacetate to a mixed solvent of 3 mL of acetone and 9 mL of N,N-dimethylformamide, then add 1 g of thermoplastic polyurethane (TPU), stir magnetically for 12 h to mix evenly, seal the beaker with a sealing film during the stirring process to prevent the solvent from volatilizing, until the solvent is completely dissolved to obtain an electrospinning solution;
[0045] S2, the electrospinning solution was transferred into the syringe, and the electrospinning parameters were set as follows: the distance between the syringe needle and the roller collection device was 15 cm, the voltage was 18 / -2 kV, the spinning solution feed rate was 1.5 ml / h, the spinning time was 2h, and the copper trifluoroacetate / TPU composite fiber membrane was prepared by electrospinning technology;
[0046] S3. The prepared copper trifluoroacetate / TPU composite fiber membrane was placed in an ascorbic acid aqueous solution with a concentration of 600 mg / mL and heated at 90 °C for a reduction reaction for 30 min. After the reaction, it was rinsed with deionized water and placed in a blast drying oven at 60 °C for 2 h to obtain a conductive Cu / TPU nanofiber membrane. The electromagnetic shielding performance in the 8.2-18 GHz band is 70 dB.
[0047] Example 3
[0048] This embodiment provides a method for preparing an elastic conductive nanofiber-based composite material, comprising the following steps:
[0049] S1. Add 2 g of silver nitrate to a mixed solvent of 3 mL of tetrahydrofuran and 9 mL of N,N-dimethylformamide, then add 1 g of polyether polyurethane (TPEU), stir magnetically for 12 h to mix evenly, seal the beaker with a sealing film during stirring to prevent the solvent from volatilizing, until the solvent is completely dissolved to obtain an electrospinning solution;
[0050] S2, the electrospinning solution was transferred into the syringe, and the electrospinning parameters were set as follows: the distance between the syringe needle and the roller collection device was 20 cm, the voltage was 22 / -2 kV, the spinning solution feed rate was 3 ml / h, the spinning time was 2h, and the silver nitrate / TPEU composite fiber membrane was prepared by electrospinning technology;
[0051] S3. The prepared silver nitrate / TPEU composite fiber membrane was placed in a sodium borohydride aqueous solution with a concentration of 800 mg / mL and heated at 60°C for a reduction reaction for 60 min. After the reaction, it was rinsed with deionized water and placed in a blast drying oven at 60°C for 2 h to obtain a conductive Ag / TPEU nanofiber membrane. The electromagnetic shielding performance in the 8.2-18 GHz band is 75 dB.
[0052] Comparative Example 1
[0053] This comparative example is the same as Example 1 except that the high molecular polymer used in this comparative example is polyacrylonitrile (PAN), and a conductive Ag / PAN nanofiber membrane is prepared. The specific type of polyacrylonitrile selected in this comparative example cannot achieve the technical effect claimed by the present invention, and the electromagnetic shielding performance in the band range of 8.2-18 GHz is only greater than 10 dB.
[0054] Comparative Example 2
[0055] This comparative example is the same as Example 1 except that the high molecular polymer used in this comparative example is polyvinyl alcohol (PVA), and a conductive Ag / PVA nanofiber membrane is prepared. The specific type of polyvinyl alcohol selected in this comparative example cannot achieve the technical effect claimed by the present invention, and the electromagnetic shielding performance in the band range of 8.2-18 GHz is only greater than 10 dB.
[0056] The elastic conductive nanofiber-based composite material prepared in Example 1 was subjected to microstructural analysis, and its SEM image is shown in FIG. Figure 1 As shown. Figure 1 The uniform loading of nanoparticles on nanofibers plays an important role in building a continuous conductive network. In addition, the abundant and interconnected pores between nanofibers enhance the absorption loss of electromagnetic waves, which can effectively absorb and reflect electromagnetic waves.
[0057] Figure 2 The XRD pattern of the elastic conductive nanofiber-based composite material prepared in Example 1 shows obvious diffraction peaks at 38.7, 44.9, 64.9, 77.9 and 81.9°, which correspond to the (111), (200), (220), (311) and (222) crystal planes of Ag, respectively, proving the successful reduction of Ag.
[0058] Figure 3This is a graph showing the electromagnetic shielding performance of the elastic conductive nanofiber-based composite material prepared in Example 1 at 8.2-18 GHz. It can be concluded that the shielding performance of Example 1 is about 95 dB, which meets the requirements of commercial electromagnetic shielding materials.
[0059] FIG4 is a physical display of the elastic conductive nanofiber-based composite material prepared in Example 1 under different strains. Due to its excellent stretchability and elasticity, the composite material can be easily stretched to 100% strain length without breaking.
[0060] Figure 5 The tensile stress-strain curve of the elastic conductive nanofiber-based composite material prepared in Example 1. The composite material has a tensile strength of 3.7 MPa and an elongation at break of 107%, showing excellent mechanical properties.
[0061] Figure 6 The temperature variation curve of the elastic conductive nanofiber-based composite material prepared in Example 1 under a DC voltage of 0.65 V is shown as a function of time. It can be concluded that the composite material can be rapidly heated to 85.6°C after being energized, and has good electrothermal conversion capability.
[0062] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for preparing an elastic conductive nanofiber-based multifunctional composite membrane material, characterized in that: include: Step S1, adding a metal salt to an organic mixed solvent and mixing evenly, then adding a high molecular polymer and continuing to mix to obtain an electrospinning solution; Step S2, injecting the electrospinning solution into a syringe to prepare a metal salt / polymer nanofiber composite membrane by electrospinning; Step S3, placing the prepared metal salt / nanofiber composite membrane in a reducing solution for reduction, and obtaining a metal / nanofiber composite membrane after drying.
2. The method according to claim 1, characterized in that In step S1, the metal salt is selected from at least one of silver nitrate, silver trifluoroacetate, silver acetate, and copper trifluoroacetate; the high molecular polymer is selected from polyurethane or polyester rubber with hydroxyl groups; and the organic mixed solvent is selected from two or more of acetone, dichloromethane, N,N-dimethylformamide, and tetrahydrofuran.
3. The method according to claim 1, characterized in that In step S1, the concentration of the metal salt in the electrospinning solution is 1-13 wt%.
4. The method according to claim 1, characterized in that In step S2, the process conditions of the electrospinning process are voltage 10~22 kV, propulsion speed 0.1~3 mL / h, receiving distance 10~20 cm, temperature 20~60 °C, and humidity 5%~40%.
5. The method according to claim 1, characterized in that In step S3, the reducing solution is selected from at least one of sodium borohydride, ascorbic acid, and hydrazine hydrate; the mass concentration of the reducing solution is 50 mg / mL~800 mg / mL, the reduction time is 5~60min, and the reduction temperature is 25~90°C.
6. An elastic conductive nanofiber-based multifunctional composite membrane material prepared according to the method according to any one of claims 1 to 5.
7. The composite membrane material according to claim 6, characterized in that: The thickness of the composite film material is less than 0.25 mm, and the electromagnetic shielding performance is greater than 95 dB when the metal content is less than 37%.
8. The composite membrane material according to claim 6, characterized in that: The composite membrane material can be quickly heated to above 85°C under a DC voltage of 0.65 V; it has a high air permeability of more than 8.2 mm / s and a thermal conductivity of more than 3880 g / (m 2 ·24h) high moisture permeability.
9. The composite membrane material according to claim 6, characterized in that: The tensile strength of the composite material reaches 3.7 MPa and the elongation at break reaches 107%.
10. Application of the elastic conductive nanofiber-based multifunctional composite membrane material according to any one of claims 6 to 9 in microelectronic devices, wearable devices for the human body, and aerospace fields.
Citation Information
Patent Citations
Metal nano self-assembly fiber material as well as preparation method and application thereof
CN114875497A
Flexible sensing composite fiber membrane with multistage microstructure as well as preparation method and application of flexible sensing composite fiber membrane
CN116240678A
Electrical spinning method for making metal nanometer particles in order in high-polymer nanometer fibre
CN1584135A
Method for manufacturing metal NANO fiber using electrospan fiber containing metal salt
KR101847477B1
Textile elastic conductible fiber membrane, textile pressure sensor and smart switch comprising thereof
TW201741512A